Effect of Intravenous Lidocaine on the Neuropathic Pain of Failed Back Surgery Syndrome - Park, Chan Hong (The Korean Pain Society, 2012)
BACKGROUND: An intravenous infusion of lidocaine has been used on numerous occasions to produce analgesia in neuropathic pain. In the cases of failed back surgery syndrom, the pain generated as result of abnormal impulse from the dorsal root ganglion and spinal cord, for instance as a result of nerve injury may be particularly sensitive to lidocaine. The aim of the present study was to identify the effects of IV lidocaine on neuropathic pain items of FBSS. METHODS: The study was a randomized, prospective, double-blinded, crossover study involving eighteen patients with failed back surgery syndrome. The treatments were: 0.9% normal saline, lidocaine 1 mg/kg in 500 ml normal saline, and lidocaine 5 mg/kg in 500 ml normal saline over 60 minutes. The patients underwent infusions on three different appointments, at least two weeks apart. Thus all patients received all 3 treatments. Pain measurement was taken by visual analogue scale (VAS), and neuropathic pain questionnaire. RESULTS: Both lidocaine (1 mg/kg, 5 mg/kg) and placebo significantly reduced the intense, sharp, hot, dull, cold, sensitivity, itchy, unpleasant, deep and superficial of pain. The amount of change was not significantly different among either of the lidocaine and placebo, or among the lidocaine treatments themselves, for any of the pain responses, except sharp, dull, cold, unpleasant, and deep pain. And VAS was decreased during infusion in all 3 group and there were no difference among groups. CONCLUSIONS: This study shows that 1 mg/kg, or 5 mg/kg of IV lidocaine, and palcebo was effective in patients with neuropathic pain attributable to FBSS, but effect of licoaine did not differ from placebo saline.